Oleic acid enhancement of Moringa oleifera seed oil by enzymatic transesterification and fractionation - Mohammed, Abdulkarim Sabo; Lai, Oi Ming; Syed Muhammad, Sharifah Kharidah; Long, Kamariah; Mohd Ghazali, Hasanah (Universiti Putra Malaysia Press, 2007)
Solvent-extracted Moringa oleifera seed oil was transesterified using immobilized lipase (Lipozyme IM 60) (Novozymes Bagsvaerd Denmark) at 1% (w/w) concentration, shaken at 60oC and 200 rpm for up to 24h. After transesterification, the oil was fractionated with acetone at -18oC and without acetone at 10oC to obtain two fractions, stearin and olein fractions. Incubation of the transesterified oil at 10oC for 24 h resulted in the formation of fat crystals, which settled at the bottom of the flask in sample transesterified for 24 h, while the control (0 h) sample became rather viscous with fat crystals in suspension. Transesterification resulted in a change in the triacylglycerol (TAG) profile of the oil, which in turn affected its solid fat content (SFC) and thermal behavior. The SFC value at 0oC after 24 h of reaction was 10.35% and significantly (P<0.05) higher than the control (0 h) (7.94%). The oil remained liquid at 20oC for all reaction times. The melting point shifted from 18.9oC for the unreacted oil to 20.5oC for oil transesterified for 24 h. Transesterification of the oil also resulted in a significant (P<0.05) increase in the crystallization temperature of the high melting glycerides from the original value of 1.6oC to 12.9oC after transesterification for 24 h. The olein and the stearin fractions obtained after the transesterified oil was fractionated with acetone at -18oC and without acetone at 10oC had different properties. The olein fraction of oil fractionated at -18oC had a significantly higher (P<0.05) oleic acid (75.2%) compared to that of fractionation without acetone at 10oC (70.5%) and the unreacted oil (67.9%). The relative percent unsaturated fatty acids in the olein fraction of the fractionated oil with acetone at -18oC (82.6%) was also significantly higher (P<0.05) than those of liquid fractions of reacted oil fractionated at 10oC (76.5%) and unreacted oil (71.6%), respectively.